2017
DOI: 10.1007/s12311-017-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Transcranial Direct Current Stimulation (ctDCS) Impairs Balance Control in Healthy Individuals

Abstract: The cerebellum plays an important role in the planning, initiation and stability of movements, as well as in postural control and balance. Modulation of neural regions underlying balance control may be a potential alternative to treat balance impairments in cerebellar patients. Transcranial direct current stimulation (tDCS) is a noninvasive and safe tool capable to modulate cerebellar activity. We aim to investigate the effects of cerebellar tDCS (ctDCS) on postural balance in healthy individuals. Fifteen heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 15 publications
2
40
0
2
Order By: Relevance
“…() also investigated the effect of one‐session prefrontal tDCS on center of pressure (COP) fluctuations during single and dual tasks and showed increased COP complexity and postural control improvement during tDCS intervention in older adults (Zhou et al ., ). A number of some studies also investigated the effect of cerebellar tDCS on posture and balance in healthy individuals (Inukai et al ., ; Foerster et al ., ). Similar to our study, static and dynamic postural stability were assessed by BBS before and immediately after cerebellar tDCS in healthy individual (Foerster et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…() also investigated the effect of one‐session prefrontal tDCS on center of pressure (COP) fluctuations during single and dual tasks and showed increased COP complexity and postural control improvement during tDCS intervention in older adults (Zhou et al ., ). A number of some studies also investigated the effect of cerebellar tDCS on posture and balance in healthy individuals (Inukai et al ., ; Foerster et al ., ). Similar to our study, static and dynamic postural stability were assessed by BBS before and immediately after cerebellar tDCS in healthy individual (Foerster et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A number of some studies also investigated the effect of cerebellar tDCS on posture and balance in healthy individuals (Inukai et al ., ; Foerster et al ., ). Similar to our study, static and dynamic postural stability were assessed by BBS before and immediately after cerebellar tDCS in healthy individual (Foerster et al ., ). This study reported static postural control changes and increased overall PSI by cerebellar cathodal tDCS in healthy individuals (Foerster et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of these articles relate to the investigations of the physiological mechanisms of cerebellar stimulation in a healthy population. These studies focus primarily on different motor functions such as visuomotor adaptation [16], motor learning [17], or balance control [18], but some also focus on cognitive functions such as probabilistic classification learning [19], verb generation [20], or attentional control [21]. Recently, Oldrati and Schutter [22] published a quantitative review of 32 shamcontrolled studies employing cerebellar tDCS to modulate both motor-and non-motor-related cerebellar functions.…”
Section: Introductionmentioning
confidence: 99%